Effects of drought stress on water consumption of poplar trees in an oasis shelterbelt of the Northwest China - Fu, Shuai; Li, Haifeng (International Journal of Agricultural and Biological Engineering, 2021)
The shelterbelt is an indispensable component of the oasis ecological system. However, drought stress can cause a large-scale decline in oasis shelterbelts. In this study, meteorological data, sapflow and soil moisture were measured to analyze the effect of drought stress on the water consumption of the oasis shelterbelt in the northwest China. Results showed that the most critical factor affecting the water consumption of an oasis shelterbelt is solar radiation, followed by relative humidity, temperature and precipitation, while the weakest factor is rainfall. Water consumption increases with solar radiation and air temperature rising, decreases with relative humidity increasing. A power index relationship between Poplar water consumption (Tr) and soil volumetric moisture content (SW) was found, which is expressed as follows: Tr=11.52/[1+e(-0.609SW+13.17)]. Meteorological and soil drought stress severely restrict oasis shelterbelt water consumption. An improved understanding of the relationship between water consumption and drought stress in oasis shelterbelts would be beneficial for irrigation managements.Keywords: oasis shelterbelt, water consumption, irrigation management, drought stressDOI: 10.25165/j.ijabe.20211406.5892Citation: Fu S, Li H F. Effects of drought stress on water consumption of poplar trees in an oasis shelterbelt of the Northwest China. Int J Agric & Biol Eng, 2021; 14(6): 109–114.